2018
DOI: 10.1093/jnci/djy126
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma-Derived Protein-Metabolite Multiplexed Panel for Early-Stage Pancreatic Cancer

Abstract: A metabolite panel in combination with CA19-9, TIMP1, and LRG1 exhibited substantially improved performance in the detection of early-stage PDAC compared with a protein panel alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 31 publications
4
96
0
1
Order By: Relevance
“…Little is known about HIST1H2BK in previous cancer studies. For certain markers identified here, their potential for non-invasive cancer diagnosis has been reported previously, such as serum TIMP1 and FGA proteins used for the diagnosis of PDAC and gastric cancer, respectively 36–38. Collectively, these results suggested that plasma EVs contain a considerable number of exLRs that are potential biomarkers for PDAC detection.…”
Section: Discussionsupporting
confidence: 74%
“…Little is known about HIST1H2BK in previous cancer studies. For certain markers identified here, their potential for non-invasive cancer diagnosis has been reported previously, such as serum TIMP1 and FGA proteins used for the diagnosis of PDAC and gastric cancer, respectively 36–38. Collectively, these results suggested that plasma EVs contain a considerable number of exLRs that are potential biomarkers for PDAC detection.…”
Section: Discussionsupporting
confidence: 74%
“…One study found a panel of six metabolites including 5-hydroxytryptophan can distinguish benign pancreatic diseases from early-stage cancer with high accuracy (34). Another study showed that a metabolite panel that includes decreased indole derivatives significantly increased the discriminating capacity of plasma protein biomarkers (35). In this study, we found that the serum levels of indole showed the largest reduction in cases in comparison with controls.…”
Section: Discussionsupporting
confidence: 50%
“…These genes included the previously described PDA growth-promoting genes, as well as the spermine/spermidine acetyltransferase SAT1 , and PP2A subunit B isoform δ ( PPP2R2D ). SAT1 modulates cell migration and resistance in multiple tumor types, while PPP2R2D is a component of the tumor suppressive phosphatase PP2A 6166 . With the exception of PPP2R2D , which displayed significant 3’-UTR lengthening and downregulation in tumors, all of the validated genes were significantly shortened and overexpressed in the TCGA-PAAD dataset.…”
Section: Resultsmentioning
confidence: 99%